Development and validation of the game performance evaluation tool (gpet) in soccer - García López, Luis Miguel; González Villora, S.; Gutiérrez D.; Serra, J. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2013)
The objective of this article is to present the Game Performance Evaluation Tool (GPET) and the results of the validation and reliability processes said tool has undergone in order to be classified as a scientific evaluation tool. The GPET measures decision-making and the execution of technical-tactical actions in invasion games/sports. The version discussed herein is specific to football. The most significant contribution made by the GPET to the assessment of game performance is that it adopts a situated view to the basic tactical principles or problems proposed by Bayer (1992) with regard to attacking, retaining possession of the ball, advancing on the opposing goal and achieving the objective. Content validity was determined, and concurrent validity, intra-observer reliability (stability) and inter-observer reliability were measured. This evaluation tool has been shown to be a suitable means for assessing the tactical and technical behaviour of both on-the-ball and off-the-ball attackers.